Efficacy and Safety of Recombinant Human Thrombopoietin on Sepsis Patients With Thrombocytopenia: A Systematic Review and Meta-Analysis - Zhang, Jin; Lu, Zongqing; Xiao, Wenyan; Hua, Tianfeng; Zheng, Yao; Yang, Min (Frontiers in Pharmacology, 2020)
The efficacy and safety of administration of recombinant human thrombopoietin (rhTPO) in sepsis patients combined with thrombocytopenia was still inconclusive.To investigate whether rhTPO is benefit for sepsis patients with thrombocytopenia. Conclusions: Current evidence shown that, rhTPO can increase PCs on 7 th day of treatment and reduce the transfusion volume of blood products in septic thrombocytopenia during hospitalization. The conclusions are needed to be verified indeed by more multicenter RCTs due to the limitation of the included studies.